2019
DOI: 10.1080/23273798.2019.1676455
|View full text |Cite
|
Sign up to set email alerts
|

Going places in Dutch and mandarin Chinese: conceptualising the path of motion cross-linguistically

Abstract: We study to what extent linguistic differences in grammatical aspect systems and verb lexicalisation patterns of Dutch and mandarin Chinese affect how speakers conceptualise the path of motion in motion events, using description and memory tasks. We hypothesised that speakers of the two languages would show different preferences towards the selection of endpoint-, trajectory-or location-information in Endpoint-oriented (not reached) events, whilst showing a similar bias towards encoding endpoints in Endpoint-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(63 reference statements)
0
5
1
Order By: Relevance
“…However, spatiotemporal continuity of the central object was necessary to induce false recognition of the moment of release with or without additional causal implication. Whereas some work, particularly in language development, has argued that the goal or end point of a movement plays a particularly critical role in encoding events in memory (Lakusta & Landau, 2005), our results indicate that information about object trajectory itself is critical to forming a coherent event representation (see also Liao, Flecken, Dijkstra, and Zwaan, 2020).…”
Section: Ball Invisiblecontrasting
confidence: 61%
“…However, spatiotemporal continuity of the central object was necessary to induce false recognition of the moment of release with or without additional causal implication. Whereas some work, particularly in language development, has argued that the goal or end point of a movement plays a particularly critical role in encoding events in memory (Lakusta & Landau, 2005), our results indicate that information about object trajectory itself is critical to forming a coherent event representation (see also Liao, Flecken, Dijkstra, and Zwaan, 2020).…”
Section: Ball Invisiblecontrasting
confidence: 61%
“…It has progressive constructions, such as the aan-het construction and postural verb constructions (e.g., zitten te + infinitive), but they are less frequently used and hence more marked than the simple forms in Dutch (Flecken, 2011). They are often constrained by more contexts and more situation types than the simple forms (see event description studies in Flecken, 2011;Liao, Flecken, Dijkstra, & Zwaan, 2020;von Stutterheim, Carroll, & Klein, 2009). For instance, von Stutterheim et al (2009) found that, when describing a motion event in which the agent moves in relation to a reference object, Dutch speakers exclusively used the simple present tense (e.g., Hij loopt naar/richting het station) instead of a progressive construction (e.g., Hij is naar/richting het station aan het lopen).…”
Section: 1 T W O D U T C H D I R E C T I O N a L P R E P O S I T mentioning
confidence: 99%
“…2004; Gerwien & von Stutterheim 2018; Liao et al. 2019; von Stutterheim & Nüse 2003). However, causation in event segmentation appears to be under‐examined (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published literature concerning event segmentation across languages concentrated on self-initiated events (e.g. Bohnemeyer et al 2007;Carroll et al 2004;Gerwien & von Stutterheim 2018;Liao et al 2019;von Stutterheim & N€ use 2003). However, causation in event segmentation appears to be under-examined (e.g.…”
Section: Introductionmentioning
confidence: 99%